2004
DOI: 10.1029/2004gl020025
|View full text |Cite
|
Sign up to set email alerts
|

Deliquescence and crystallization of ammonium sulfate‐glutaric acid and sodium chloride‐glutaric acid particles

Abstract: [1] In the following, we report the deliquescence relative humidities (DRH) and crystallization relative humidities (CRH) of mixed inorganic-organic particles, specifically ammonium sulfate-glutaric acid and sodium chlorideglutaric acid particles. Knowledge of the DRH and CRH of mixed inorganic-organic particles is crucial for predicting the role of aerosol particles in the atmosphere. Our DRH results are in good agreement with previous measurements, but our CRH results are significantly lower than some of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
93
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(103 citation statements)
references
References 21 publications
8
93
1
Order By: Relevance
“…Hence, the DRH of the system was slightly lowered relative to the pure components. The decreased DRH has also been confirmed by studies which observed values ranging from 77 to 78.5% RH (Prenni et al 2003;Pant et al 2004;Zardini et al 2008). Moreover, water absorption started at about 70% RH.…”
Section: Hygroscopicitysupporting
confidence: 63%
See 1 more Smart Citation
“…Hence, the DRH of the system was slightly lowered relative to the pure components. The decreased DRH has also been confirmed by studies which observed values ranging from 77 to 78.5% RH (Prenni et al 2003;Pant et al 2004;Zardini et al 2008). Moreover, water absorption started at about 70% RH.…”
Section: Hygroscopicitysupporting
confidence: 63%
“…During the growth process, the abrupt increase in both the ν(C=O) peak's position and fwhh at 67% RH indicates deliquescence, consistent with Peng's bulk measurement of 65.3% RH and Braban's determination of 69% RH (Peng et al 2001;Braban et al 2003). For GA, the CRH has been reported as 29-33% (Peng et al 2001) and 22.5-36% (Pant et al 2004). Deliquescence has been observed between 83 and 90% RH (Zardini et al 2008 and the references therein).…”
Section: Phase Transitions Of Single-component Systemssupporting
confidence: 62%
“…Sjogren et al (2004) found that (NH 4 ) 2 SO 4 -adipic acid particles (50 wt% and 76wt% adipic acid) exhibited a lower G f at a residence time of less than 4 s than the G f at more than 4 s at 78-91%RH after deliquescence. Xiong et al (1998) found that submicrometer sulfuric acid (H 2 SO 4 ) particles attained their equilibrium size within 6 s. On the other hand, the G f of H 2 SO 4 particles coated with three monolayers of lauric acid further increased as the residence time increased from 6 s to 10 s, providing evidence that the coated H 2 SO 4 particles had not yet reached their equilibrium size within 6 s. Organic films can act a physical barrier to retard the water condensation (or evaporation) rate in planar solutions and on particle surfaces (Gill et al, 1983;Barnes, 1986) and can lower the accommodation coefficient (Pandis et al, 1995). A summary of laboratory studies on the evaporation and condensation rates of water vapor from particles in the presence of organic films has been presented by Chuang (2003).…”
Section: Laboratory Measurementsmentioning
confidence: 99%
“…A summary of laboratory TDMA studies has been presented in Table 1. Other techniques include single particle mass spectrometry (Ge et al, 1996(Ge et al, , 1998, ambient-dry aerosol size spectrometer (Stanier et al, 2004), RH-controlled nephelometry (ten Brink et al, 2000), aerosol cell-microscope system (Pant et al, 2004;Parsons et al, 2004), aerosol flow tube-Fourier Transform Infrared (FTIR) system (Brooks et al, 2003;Braban and Abbatt, 2004), RHcontrolled optical particle counter Hand et al, 2000;Kreisberg et al, 2001), filter-based analysis by beta attenuation (or gravitational method) (Hitzenberger et al, 1997;Speer et al, 1997), and water activity measurements of bulk aqueous solutions (Brooks et al, 2002;Wise et al, 2003;Marcolli et al, 2004). We focus our discussions on TDMA measurements in this paper.…”
Section: Introductionmentioning
confidence: 99%
“…Zuend et al: Computation of LLE and gas/particle partitioning of aerosols While the most prevalent inorganic aerosol components are well established (Zhang et al, 2007;Russell et al, 2009), the organic fraction can consist of a large number of different compounds (Goldstein and Galbally, 2007), containing functional groups such as alkyl, hydroxyl, carboxyl, carbonyl, and aromatic groups (Rogge et al, 1993;Saxena and Hildemann, 1996;Yu et al, 1999;Decesari et al, 2000;Griffin et al, 2002;Decesari et al, 2006;Russell et al, 2009). Non-ideal interactions between organic and inorganic species in the liquid aerosol phase affect water uptake (Saxena et al, 1995;Clegg et al, 2001;Zuend et al, 2008), may induce phase separation (Pankow, 2003;Erdakos and Pankow, 2004;Chang and Pankow, 2006;Marcolli and Krieger, 2006), affect efflorescence and deliquescence behaviour (Choi and Chan, 2002;Chan and Chan, 2003;Pant et al, 2004;Parsons et al, 2004;Marcolli and Krieger, 2006;Ling and Chan, 2008), and influence the gas/particle partitioning of semivolatile compounds (Saxena and Hildemann, 1997;Turpin et al, 2000;Cocker et al, 2001;Bowman and Melton, 2004;Chang and Pankow, 2006). Moreover, liquid and solid phases present in aerosol particles provide reaction media for heterogeneous and multiphase chemistry (Ravishankara, 1997;Kalberer et al, 2004;Barsanti and Pankow, 2004;Knopf et al, 2005;Herrmann et ...…”
mentioning
confidence: 99%